Cognitive selection mechanism performance in IEEE 802.11 WLAN - Hashim, Wahidah; Ismail, Ahmad Fadzil; Ghafar, Nadratul; Dzulkifly, Sumayyah (International Association of Computer Science and Information Technology Press, 2013)
Recent growth in Wireless Local Area Network (WLAN) usage has generated considerable interest in the establishment of the IEEE 802.11 WLAN standards. WLAN has been developed with the capability to handle tremendous growth of data traffic and therefore have been proliferating worldwide. The influencing factors and the parameters involved prior choosing which access point (AP) to connect with are to be carefully evaluated and dealt with in the process of WLAN deployment. Properly designed selection mechanisms that able to provide not only radio coverage but also a good internet connection speed are in turn expected to be able to improve the Quality of Service (QoS). In this paper, a new approach for the AP selection in IEEE 802.11 is proposed. The new technique takes into account internet connection speed in contrast to the classic approach that solely based on the Received Signal Strength (RSS). A heuristic selection model was developed namely Evaluative AP Selection which used LINUX Bash script programming whilst the internet connection speed test was ran by means of PHP script. The results for the selection were evaluated respectively to see the variation in selection pattern when compared to the default selection algorithm. The time interval during the scanning and selection process was also analysed in the investigation to further identify the performance of the model. The enhancement reaped from the developed selection algorithm is expected to bring benefit to different user at various places